Biological Observations of Himertula vidhyavathlae Sp. Nov (Orhtoptera : Tettigoniidae : Phaneropterinae) under Laboratory Conditions - Senthilkumar, N.; Karthikeyan, A.; Sanjayan, K. P.; Mahalingam, V.; Muralirangan, M. C. (Indian Forester, 2004)
From a global perspective the Tettigoniids or the Long-horned grasshoppers, appear to be a lesser known group of orthopteroid insects, probably because of the difficulties in sampling, laboratory rearing, and also because of its behavioural and ecological uniqueness. Available information on the bioecological characteristics of tettigoniids around the world is very meager. Moreover, no record is available on the biology of Tettigoniidae of Indian subcontinent. The paper presents the mating and ovipositional behaviour of tettigoniid species Himertula vidhyavathiae Ingrisch and Muralirangan, 2003.